Why Foreign Banks Fail in Emerging Economies: Risk Management Perspective from Pakistan - Shahid Mohammad, Khan Gauri; Omar, Masood; Kiran, Javaria (2019)
The tenacity of this paper is to understand the concept of ‘relative efficiency’ as an alternative measure to assess bank performance, and to investigate the progressive performance of foreign and domestic banks in Pakistan. A very steady growth is observed in assets of foreign banks in Pakistan although Pakistani banking sector has very limited contribution of foreign banks but its historic contribution is much accountable towards economic growth. The significance of this study is that we have conducted the study in Pakistan which was not explored earlier. A research design is the structure for investigation and way of finding out the answer of research question (Huizinga, 1999). We have conducted this research under the umbrella of Quantitative paradigm. Our preferred methodology is CAMELS. This system was developed by ACCION (Americans for Community Co-operation in Other Nations) in 1980’s to help regulator banks of North America (hUallachain, 1994). CAMELS methodology adopted by North America Bank regulators to know the financial and managerial reliability of commercial lending institutions. For sample selection of the banks, we used criteria sampling method that is a type of non-probability sampling. We took sample data of 16 banks working in Pakistan from the period of 2014-2016. Groups are structured according to their ownership status. After assessment of CAMELS rating system in the context of Pakistan banking industry, it is observed that CAMELS is an internal rating system and its results are not available to the general public but to the regulators and the directors of the banks, so we implement its ratios to avail the result of the sample banks. Results of international credit rating agencies such as S&P, Moody’s and Fitch should also be compare for similarities with CAMELS or any of the supervisory rating systems implemented in different countries. It would be productive research to study adoptability of CAMELS rating system in the context of Islamic banking system..